'When Cryptococcus strikes and lupus is found': a unique covert unveiling of systemic lupus erythematosus presenting as subacute meningitis. (July 2022) - Essien, Francis; Westbrook, Marquise; Wolfley, Graey; Patterson, Shane; Carrol, Matthew
Cryptococcal neoformans is a rare fungal pathogen that has been associated with immunocompromised individuals. Due to its rare occurrence, clinicians have a low index of suspicion for diagnosis, which can lead to increased morbidity and mortality. We present an 81-year-old fully functional woman with no known predisposing risk factors or previous immunocompromising conditions who was found to have cryptococcal meningitis on cerebrospinal fluid analysis in the setting of newly diagnosed uncontrolled type 2 diabetes and systemic lupus erythematosus (SLE).